Implementasi Penanaman Nilai-Nilai Moderasi Beragama Di Sekolah Dasar Agar Terwujudnya Generasi Moderat - Rudiyanto; Firdaus; Sukari (4, 2024)
Instilling the values of religious moderation from an early age is a strategic step in forming a tolerant, inclusive generation that upholds national values. This study aims to describe and analyze the implementation of instilling the values of religious moderation in elementary schools as an effort to create a moderate generation. The approach used is qualitative with descriptive methods. Data collection techniques are carried out through observation, in-depth interviews, and documentation of teachers, principals, and students in several elementary schools. The results of the study indicate that the implementation of the values of religious moderation is realized through integration in Islamic Religious Education learning, the habituation of tolerant attitudes in daily life at school, and through extracurricular activities that instill a spirit of togetherness across differences. Supporting factors include teacher commitment, school policy support, and a harmonious social environment. The obstacles faced include the lack of understanding of some teachers regarding the concept of religious moderation as a whole and external challenges in the form of the influence of social media. Systematic and sustainable instillation of the values of religious moderation in elementary schools has proven effective in forming the character of students who are moderate, tolerant, and peaceloving. Abstrak Penanaman nilai-nilai moderasi beragama sejak dini menjadi langkah strategis dalam membentuk generasi yang toleran, inklusif, dan menjunjung tinggi nilai-nilai kebangsaan. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis implementasi penanaman nilai-nilai moderasi beragama di sekolah dasar sebagai upaya mewujudkan generasi moderat. Pendekatan yang digunakan adalah kualitatif dengan metode deskriptif. Teknik pengumpulan data dilakukan melalui observasi, wawancara mendalam, dan dokumentasi terhadap guru, kepala sekolah, dan peserta didik di beberapa sekolah dasar. Hasil penelitian menunjukkan bahwa implementasi nilai moderasi beragama diwujudkan melalui integrasi dalam pembelajaran Pendidikan Agama Islam, pembiasaan sikap toleran dalam kehidupan sehari-hari di sekolah, serta melalui kegiatan ekstrakurikuler yang menanamkan semangat kebersamaan lintas perbedaan. Faktor pendukung meliputi komitmen guru, dukungan kebijakan sekolah, serta lingkungan sosial yang harmonis. Adapun kendala yang dihadapi antara lain kurangnya pemahaman sebagian guru terhadap konsep moderasi beragama secara utuh serta tantangan eksternal berupa pengaruh media sosial. Penanaman nilai moderasi beragama secara sistematis dan berkelanjutan di sekolah dasar terbukti efektif dalam membentuk karakter peserta didik yang moderat, toleran, dan cinta damai.